2020
DOI: 10.3390/f11050486
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Deadwood Microsites in Areas Designated under the Habitats Directive (Natura 2000)

Abstract: The continuing decline in biodiversity presents a major environmental protection challenge. The conservation of sufficiently extensive and diverse habitats requires an array of coordinated actions, often involving large areas. While a set of conservation objectives have been defined for the Natura 2000 network, no universal methods of accomplishing them have been specified, and so they must be designed by individual Member States. Deadwood volume and the density of large deadwood pieces are widely used for eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In Tanzania, Gizachew et al [9] found that most PAs were effective in reducing deforestation rates, even if there were important pressures in their surrounding lands. In Europe, Bujoczek et al [10] found that the quality of forest habitats under strict and active protected status in the regions was enhanced relative to that of managed forests. In Serbia, Maruna et al [11] describe the historical context of forest planning and management processes and discuss how the concept of land use planning for urban forest protection was established in the country through the critical re-assessment of the institutional structure of land use planning in a post-socialist environment.…”
mentioning
confidence: 99%
“…In Tanzania, Gizachew et al [9] found that most PAs were effective in reducing deforestation rates, even if there were important pressures in their surrounding lands. In Europe, Bujoczek et al [10] found that the quality of forest habitats under strict and active protected status in the regions was enhanced relative to that of managed forests. In Serbia, Maruna et al [11] describe the historical context of forest planning and management processes and discuss how the concept of land use planning for urban forest protection was established in the country through the critical re-assessment of the institutional structure of land use planning in a post-socialist environment.…”
mentioning
confidence: 99%